Evaluating the relationship of imagery and self-confidence in female and male athletes - Rattanakoses, Raweewat; Omar Fauzee, Mohd Sofian; Soh, Kim Geok (Eurojournals, 2009)
This study examines the relationship between imagery and confidence in athletes. The Sport Imagery Questionnaire and a Self-Confidence questionnaire were used to collect data. The samples consisted of athletes who are from the Khon Kaen Sport School in Thailand and who regularly participate in sports training (5 days a week). All subjects (n=120) were selected by purposive sampling and consisted of 71 (59.2 %) male and 49 (40.8 %) female athletes. Our analysis considered two parameters, imagery and selfconfidence, which were evaluated with regards to the physical fitness level and experience of the athletes. The data was analyzed using a t-test to determine the difference of the means between imagery and self-confidence measures in males and females. Analysis of variance (ANOVA) (P<0.05) was used to evaluate differences across the groups, and linear regression and correlation analyses (r =0.71) were used to compare between genders, physical fitness, and experience levels. The results show that there are significant correlations between males and females in terms of imagery and self-confidence. This result suggests that imagery and self-confidence in male and female athletes are associated with high levels of physical fitness and more experience in sports situations.